2000
DOI: 10.1016/s0008-6363(00)00179-6
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenic activity of cardiac muscle in pulmonary veins of the dog: implication for the genesis of atrial fibrillation

Abstract: Objective: Pulmonary veins are important foci of ectopic beats to initiate paroxysmal atrial fibrillation. The purpose of this study were to investigate the electrophysiological characteristics of excitable cells in canine pulmonary veins obtained from healthy and chronic rapid atrial pacing dogs and their responses to cardioactive agents. Methods: Transmembrane action potentials (APs) were recorded from multiple sites of pulmonary veins isolated from 17 healthy dogs and 14 dogs with chronic (6-8 weeks) rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
202
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(242 citation statements)
references
References 24 publications
(17 reference statements)
38
202
0
2
Order By: Relevance
“…Application of norepinephrine accelerated the rate of spontaneously active pulmonary vein preparations. Chen et al 16 recorded spontaneously occurring action potentials at the distal end of the myocardial sleeves of pulmonary veins of the dog heart. Spontaneously occurring activity was seen in none of our preparations.…”
Section: Intracellular Recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of norepinephrine accelerated the rate of spontaneously active pulmonary vein preparations. Chen et al 16 recorded spontaneously occurring action potentials at the distal end of the myocardial sleeves of pulmonary veins of the dog heart. Spontaneously occurring activity was seen in none of our preparations.…”
Section: Intracellular Recordingsmentioning
confidence: 99%
“…This is not in contradiction to the study by Cheung 15 because automaticity was absent in his study when the pulmonary vein was electrically coupled to the atrium, as was the case in our preparations. In the study by Chen et al, 16 pulmonary veins were harvested from dog hearts after 6 to 8 weeks of rapid atrial pacing, and preparations were superfused. Differences in the preparations and techniques may well account for the differences in automaticity.…”
Section: Intracellular Recordingsmentioning
confidence: 99%
“…3 Our previous studies in multiple cells or single cells have shown that pulmonary veins (PVs) contain cardiomyocytes with or without spontaneous activities, which may underlie the high arrhythmogenic activities of PVs. 10,11 Although clinical electrophysiological study has found that the SVC and PVs may have different electrophysiological characteristics, 12 knowledge about the mechanisms underlying the arrhythmogenic activity of the SVC was limited. Because experiments utilizing intact tissue are complicated by the multiplicity of cell types and complex arrangement of cardiac cells within the tissue matrix, isolation of single SVC cardiomyocytes is important in evaluating the arrhythmogenic activity of SVC.…”
mentioning
confidence: 99%
“…No entanto, no modelo do cão submetido a pacing rápido crónico, a estimulação simpática induziu atividade repetitiva das VP e contribuiu para iniciar FA 35 . Também a estimulação combinada do simpático e parassimpático pode influenciar as propriedades eletrofisiológicas e aumentar a propensão para FA em cães 16,35 . Os efeitos eletrofisiológicos da atividade autonó-mica reflexa nas aurículas e VP podem assim ter um papel importante na fisiopatologia da FA.…”
Section: Modelos Animais E Estudo Da Vulnerabilidade Para Fibrilhaçãounclassified